HLA‐A, HLA‐B, HLA‐DRB1 allele and haplotype frequencies of 14 529 Chinese Han bone marrow donors living in Dalian, China. (5th February 2016) - Shao, L. N.; Zhang, S. T.; Yu, W. J.; Zhou, S. H.; Duan, Y.; Pan, L. Z.; Wang, N.; Hu, Y.
Summary: We investigated the allele and haplotype frequencies of HLA‐A, HLA‐B and HLA‐DRB1 loci in Dalian Chinese Han population using blood samples of unrelated marrow donors who live in Dalian. The genetic relationship between Dalian and different regions worldwide was further explored based on HLA status of different populations. A total of 14 529 samples were genotyped at 2‐digit level only by sequence‐specific oligonucleotide and sequence‐based typing methods. Allele frequencies of HLA‐A, HLA‐B and HLA‐DRB1 were calculated by the direct counting method. Haplotype frequencies and linkage disequilibrium (LD) values were calculated by the maximum likelihood method. F ST values were calculated by allele frequency data of each locus. Phylogeny tree of Nei's D A genetic distances was constructed by the UPGMA method. HLA‐A*02 was the most frequent allele at HLA‐A locus followed by A*11 and A*24. Alleles at HLA‐B locus ranked in decreasing order by frequency were B*40, B*15 and B*13. The three highest frequency alleles were DRB1*15, DRB1*09 and DRB1*12 at HLA‐DRB1 locus. A*30‐B*13‐DRB1*07 was the most frequent three‐locus haplotype. For the population relationships, Dalian had a relative close genetic relationship with Liaoning and Yantai‐Weihai and a relative distant genetic relationship with Australia. The information obtained in this study may provide useful information for anthropological studies, for disease‐association studies and helping bone marrow transplantation patients to search HLA‐matched donors.